ASESMEN KEMAMPUAN MENGENAL HURUF ANAK USIA DINI MELALUI MEDIA BIGBOOK - Risnita Risnita; Winda Oktaviana (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
The ability to recognize letters is an important ability developed in children to prepare children to enter the next level of education. This study aims to develop the ability to recognize the letters in children using big book media in Mutiara Almadani Kindergarden. This research uses classroom action research approach (collaborative classroom action research). The study population is children of Mutiara Almadani Kindergarten Sungai Penuh City which amounts to 200 people which is divided into 10 study groups and sampling technique is cluster sampling, that is B3 group which is 20 children. Data collection techniques are observation, interview, documentation, and field notes. Data analysis technique used in this research is quantitative analysis with percentage and qualitative analysis. The results showed that there was an increase in the ability to recognize letters that is in the initial condition of 45% increase in cycle I to 60,42%, in cycle II increased by 75% and in cycle III to 88,33% with very developed criteria good. Thus it can be concluded that the media big book can develop the ability to recognize the letters of children in Mutiara Almadani Kindergarten Sungai Penuh City.